Acute acalculous cholecystitis in a 17-year-old girl with Epstein-Barr virus infection - Pawłowska-Kamieniak, Agnieszka; Mroczkowska-Juchkiewicz, Agnieszka; Gołyska, Dorota; Kominek, Katarzyna; Pac-Kozuchowska, Elżbieta (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
Acute cholecystitis is most frequently concomitant with cholelithiasis, whereas acute acalculous cholecystitis is usually of an infectious aetiology. Among the aetiological factors, Epstein-Barr virus (EBV) infection is also mentioned. The case of a 17-year-old girl is described, hospitalised in the Children’s Clinical Hospital, Paediatric Clinic, at the Medical University in Lublin, due to fever, upper abdomen pain lasting for a week, and nausea for several days. Based on the diagnostic – laboratory tests performed and ultrasonographic examination, acute acalculous cholecystitis was diagnosed, taking course with elevated aminotransferase activity and features of cholestasis. Serological tests confirmed an acute infection with Epstein-Barr virus. After 2 weeks of hospitalisation, the patient, receiving conservative treatment, was discharged home in good condition. A follow-up examination performed 2 weeks later did not show deviation from normal.